Representation of feminism in Miss & Mrs. Cops (John Fiske’s semiotic analysis) - Lukman Hakim; Wina Kurnia (Islamic Communication Journal, 2023)
Oppression of women is still common today. Feminism is a social movement that strives to uphold justice for women. Feminists are doing various ways to voice and resuscitate society about gender discrimination against women. Film media is one of the tools used by feminists to make people aware of the issue. Film media was chosen because the film is considered capable of influencing and shaping society based on the messages it conveys. "Miss Mrs Cops" is a blackhead action film that tells the struggle of policewomen in solving criminal cases. In the film, female characters are portrayed as conduits to convey the messages of feminism. This study aims to find out the meaning of semiotic codes regarding feminism at the level of reality, representation, and ideology. The study used qualitative research with John Fiske's semiotics analysis. The study results show that the representation of the message of feminism in this film is depicted on three levels. First, the level of reality through appearance, clothing, dialogue, environment, and behaviour. The camera provides code at both levels—representation through shooting and editing. The three levels of ideology are the thoughts or actions female characters carry. All three describe women as strong, brave, independent, and willing to do anything to defend women's rights and justice.  This study contributes to strengthening women's narratives in the public space where academically it is also a concern of Islamic communication. ***Penindasan terhadap perempuan masih sering terjadi hingga saat ini. Feminisme merupakan gerakan sosial yang berjuang dalam menegakan keadilan terhadap perempuan. Para feminis melakukan berbagai cara untuk menyuarakan dan menyadarkan masyarakat mengenai diskriminasi gender terhadap perempuan. Media film merupakan salah satu alat yang digunakan feminis untuk menyadarkan masyarakat mengenai isu tersebut. Media film dipilih karena dianggap mampu memengaruhi dan membentuk masyarakat berdasarkan pesan-pesan yang disampaikannya. Film “Miss Mrs. Cops” merupakan film action komedi yang menceritakan perjuangan polisi wanita dalam memecahkan kasus kriminal terhadap perempuan. Dalam film ini, karakter perempuan digambarkan sebagai penyalur untuk menyampaikan pesan-pesan feminisme. Tujuan penelitian ini untuk mengetahui makna kode semiotika mengenai feminisme dalam level realitas, level representasi dan level ideologi. Penelitian ini menggunakan penelitian kualitatif dengan analisis semiotika John Fiske. Hasil penelitian menunjukkan bahwa representasi pesan feminisme dalam film ini tergambar dalam tiga level. Pertama, level realitas melalui penampilan, pakaian, dialog, lingkungan, perilaku. Kedua level, representasi melalui pengambilan gambar, editing, camera memberikan kode. Ketiga level ideologi, pemikiran-pemikiran atau tindakan-tindakan yang dilakukan oleh tokoh perempuan. Ketiganya menggambarkan perempuan sebagai pribadi yang kuat, berani, mandiri dan rela melakukan apapun demi membela hak dan keadilan untuk perempuan. Kajian ini berkontribusi bagi penguatan narasi perempuan di ruang publik dimana secara akademis juga menjadi concern dari komunikasi Islam.